ANALYSIS OF SPLENIC NOTCHES IN HUMAN CADAVERS AND ITS CLINICAL RAMIFICATIONS: A CROSS-SECTIONAL STUDY - Mishra, Gopabandhu; Sahoo, Duryodhan; Dash, Lipsita (Student's Journal of Health Research Africa, 2024)
Introduction Understanding the exterior shape of the spleen anatomically is crucial for both radiological and surgical diagnosis. The superior border splenic notches are a defining trait of the spleen, yet they hardly ever go into detail to be regarded as fissures or divide the spleen into several lobes. There aren't many splenic fissures cadaveric reports to date. To determine the frequency and clinical importance of splenic notches, lobation, and fissures, this study looked at the morphological structure and anatomy of spleens removed from cadavers. Methods This cross-sectional study was conducted at the Department of Anatomy, Medical College and Hospital, Keonjhar, over one year. A total of 100 spleens were obtained from cadavers, dissected, and preserved in 10% formalin. The spleens were analyzed for notches, lobation, and fissures, and their morphological characteristics were documented. Results Of the 100 spleens studied, 40% showed notches on the superior border, while 10% exhibited notches on the inferior border. The remaining 50% had no notches on either border. Fissures were observed in 10% of the spleens. Among these, six (6%) had incomplete fissures, while four (4%) had complete fissures that divided the spleen into two lobes. The complete fissures resulted in bilobed spleens, with distinct hila for each lobe. In cases where fissures were present, they varied in depth and width, with incomplete fissures reaching depths of 0.5-1 cm without leading to lobation. Conclusion The results of this investigation shed important light on the morphology and frequency of bilobed spleens and splenic fissures. Different from other recognized splenic defects, a bilobed spleen is an uncommon congenital abnormality. When performing conservatory splenectomy procedures, surgeons might use the splenic fissures in bilobed spleens as guidance. Recommendation To lower the risk of surgical complications, we recommend a procedure of partial splenectomy in less severe cases.